THE PERCEPTION OF ENGLISH EDUCATION STUDENTS ON THE USE OF IPA SYMBOLS IN PHONETICS AND PHONOLOGY COURSE - Thiorysa, Luthfia Putri; Natasha, Harum (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This research aims to describe the perceptions of English Education students on the use of IPA (International Phonetic Alphabet) symbols in Phonetics and Phonology course at the State Islamic University of Sultan Syarif Kasim Riau. This research uses a quantitative approach with a descriptive quantitative design. The research was conducted in March 2025 at the English Education Department of the State Islamic University of Sultan Syarif Kasim. The population consisted of second-semester English education students from five classes in the academic year 2024/2025, and 38 students were selected through purposive sampling, which focused on those who had taken the course and intended to become English teachers. The data were collected using a questionnaire consisting of 24 statements. The data were analyzed using SPSS version 30. The total score was 2,916 with a mean of 76.74, which falls into the positive perception category. This indicates that students perceive the use of IPA symbols as beneficial in learning phonetics and phonology.